Seguir enseñando y aprendiendo en tiempos de pandemia: alteraciones, excepcionalidades y esperanzas en el (por) venir - Manuale, Marcela (Universidad Nacional del Litoral, 2022)
This paper originates in a reflective process linked to university teaching practices rooted in this new pandemic context. From the standpoint of university virtual teaching and my long-standing role as pedagogical advisor in the Faculty of Biochemistry and Biological Sciences, some problematic areas in these unprecedented times, full of exceptionalities, are raised.